Case report on accessary and cavitated uterine mass-a rare form of mullerian anomaly - Kalokhe, Chaitali; Bhosale, Abhijeet (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Accessory and cavitated uterine mass (ACUM) are a rare form of developmental Mullerian anomaly seen in young females with chief complaints of chronic pelvic pain and dysmenorrhea. Imaging modalities, including hysterosalpingography (HSG), ultrasonography (USG) and magnetic resonance imaging (MRI) forms the mainstay for diagnosis of this condition. It is an accessory cavity in otherwise normal uterus. It is lined by normal functional endometrium and surrounded by myometrium- like smooth muscle cells hence, it has macroscopic and microscopic resemblance to the uterus. In most of the cases, surgical treatment is recommended due to relieve the severe dysmenorrhea.